THE EFFECT OF HIGH-PROTEIN FEEDING FREQUENCY OF UFBs-RAS ON THE PRODUCTION PERFORMANCE OF GOURAMI (Osphronemus goramy) FRY: PENGARUH FREKUENSI PEMBERIAN PAKAN PROTEIN TINGGI PADA UFBs-RAS TERHADAP PERFORMA PRODUKSI BENIH GURAMI (Osphronemus goramy) - Nur Fatimatuz Zahra; Atikah Nurhayati; Irfan Zidni; Ujang Subhan (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
Gourami (Osphronemus goramy) production in intensive systems is often suboptimal because of poor feeding management and water quality. The application of a recirculation system with ultrafine bubbles (UFBs-RAS) has the potential to improve the quality of the cultivation environment. However, feeding strategies, particularly the frequency and protein content, strongly influence their effectiveness. This study aimed to determine the optimal frequency of high-protein feeding on gourami fry production performance in the UFBs-RAS system. The study was conducted over 33 days. Feed was provided at 5% biomass/day with a protein content of ± 50% according to the treatment frequency. The test fish had a length of 3 ± 0.00 cm and a weight of 0.8 ± 0.00 g, with a total of 720 fish. This study was designed using a completely randomized design (CRD) with feeding frequencies of 3, 4, and 5 times per day. Each treatment was repeated 4 times, resulting in 12 experimental units. Statistical analysis showed that feeding frequency significantly affected the production performance of gourami fry. Feeding five times per day resulted in the best production performance, with a 100% survival rate, length growth rate of 3.83 ± 0.21%, weight growth rate of 4.16 ± 0.16%, feed utilization efficiency of 127%, protein efficiency ratio of 2.56, and size variation of 9.33%. These results indicate that increasing the feeding frequency in the UFBs-RAS system can improve the nutrient utilization efficiency and optimal growth performance of gourami fry.